Maternal life stress events in pregnancy link to children's school achievement at age 10 years - Li, Jianghong; Robinson, Monique; Malacova, Eva; Jacoby, Peter; Foster, Jonathan; van Eekelen, Anke (Mosby, Inc., 2013)
Objective: To test the hypothesis that maternal antenatal exposure to life stress events is associated with lower achievement in literacy and numeracy at age 10 years, with sex differences in this link. Study design: The Western Australian Pregnancy Cohort Study recruited 2900 women at 18 weeks' pregnancy, and 2868 children were followed up at birth and postnatally. At age 10 years, information on 1038 children was linked to their literacy and numeracy test scores. Multivariate regression models were used to test the foregoing hypotheses, adjusting for important confounders. Results: In girls, maternal antenatal exposure to 4 or more maternal life stress events or death of the mother's friend and/or relative was associated with lower reading scores. In contrast, exposure to 3 or more life stress events or to a pregnancy or financial problem was associated with higher reading scores in boys. Furthermore, maternal exposure to 4 or more life stress events was associated with higher mathematic scores and a residential move was linked to higher writing scores in boys. Conclusion: Maternal antenatal exposure to life stress events has differing effects on the school performance of male and female offspring. Further research is needed to explore the reasons for this sex difference.